2011
DOI: 10.1105/tpc.109.072769
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Vacuolar Calcium Storage Mediated by CAX1 Regulates Apoplastic Calcium Concentration, Gas Exchange, and Plant Productivity in Arabidopsis    

Abstract: The physiological role and mechanism of nutrient storage within vacuoles of specific cell types is poorly understood. Transcript profiles from Arabidopsis thaliana leaf cells differing in calcium concentration ([Ca], epidermis <10 mM versus mesophyll >60 mM) were compared using a microarray screen and single-cell quantitative PCR. Three tonoplast-localized Ca 2+ transporters, CAX1 (Ca 2+ /H + -antiporter), ACA4, and ACA11 (Ca 2+ -ATPases), were identified as preferentially expressed in Ca-rich mesophyll. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
301
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(317 citation statements)
references
References 98 publications
13
301
1
2
Order By: Relevance
“…CAXs appear to be a fulcrum for modulating ion homeostasis, pH and redox levels within plant cells (Conn et al . 2011; Cho et al . 2012).…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
See 3 more Smart Citations
“…CAXs appear to be a fulcrum for modulating ion homeostasis, pH and redox levels within plant cells (Conn et al . 2011; Cho et al . 2012).…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
“…In mesophyll cells, CAXs appear to be especially important in maintaining Ca 2+ homeostasis as well as stomatal conductance (Conn et al . 2011). These phenotypes suggest that altered CAX expression misappropriates Ca 2+ within plant cells.…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Elemental analysis has also revealed that impairment of CAX1 and CAX3 caused dramatic alterations in the shoot ionome, namely elevated levels of phosphate (PO 4 3-; P i ), manganese (Mn 2+ ), and zinc (Zn 2+ ) and decreased Ca 2+ and magnesium (Mg 2+ ) ion concentrations (Cheng et al, 2005). A recent study further showed that the leaf apoplastic free Ca 2+ concentration ([Ca 2+ ]) of cax1/cax3 was 3-fold greater than that of the wild type, accounting for the phenotypes of reduced cell wall extensibility, stomatal aperture, transpiration, CO 2 assimilation, and leaf growth rate (Conn et al, 2011b). Despite no evidence yet of a direct involvement of Ca 2+ in P i signaling, the observation of an increased accumulation of P i in the cax1/cax3 mutant has provided the first link between Ca 2+ and P i homeostasis and thus drew our attention and interest to investigate the potential role of CAX1 and CAX3 in P i signaling.…”
mentioning
confidence: 99%